Evaluation of the antioxidant properties and oxidative stability of Pecorino cheese made from the raw milk of ewes fed Rosmarinus officinalis L. leaves. (4th December 2014) - Branciari, Raffaella; Ranucci, David; Trabalza‐Marinucci, Massimo; Codini, Michela; Orru, Mara; Ortenzi, Roberta; Forte, Claudio; Ceccarini, Maria R.; Valiani, Andrea
Summary The aim of this work was to study the effect of rosemary leaf dietary supplementation on the antioxidant activities and total phenolic content of Pecorino cheese. Three hundred and twenty‐four sheep were randomly assigned to two dietary groups, which received a standard diet based on lucerne hay and concentrate (400 g per day). The concentrate of the rosemary supplemented group contained 2.50% dried rosemary leaves. The trial lasted 7 weeks. Cheesemaking was performed 3, 5 and 7 weeks from the start of the trial. The Pecorino cheese antioxidant activity was modified by the diet. Rosemary supplementation increased the total phenolic content, enhanced the antioxidant properties and decreased the lipid oxidation of cheese. A slight decrease in flavour was detected in cheeses after 7 weeks of rosemary administration.